2015
DOI: 10.1088/0031-9155/60/5/1793
|View full text |Cite
|
Sign up to set email alerts
|

Calculating radiotherapy margins based on Bayesian modelling of patient specific random errors

Abstract: Collected real-life clinical target volume (CTV) displacement data show that some patients undergoing external beam radiotherapy (EBRT) demonstrate significantly more fraction-to-fraction variability in their displacement ('random error') than others. This contrasts with the common assumption made by historical recipes for margin estimation for EBRT, that the random error is constant across patients. In this work we present statistical models of CTV displacements in which random errors are characterised by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It is known that the estimation of treatment specific standard deviations from a limited number of samples only slowly converges ∼n −1/2 . The inclusion of a Bayesian prior improves the result but only slightly (Herschtal et al 2015). In other words: with a limited number of fractions, we have too little information to rule out a relatively large outlier in one of the next fractions, which might dominate the required margin.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that the estimation of treatment specific standard deviations from a limited number of samples only slowly converges ∼n −1/2 . The inclusion of a Bayesian prior improves the result but only slightly (Herschtal et al 2015). In other words: with a limited number of fractions, we have too little information to rule out a relatively large outlier in one of the next fractions, which might dominate the required margin.…”
Section: Discussionmentioning
confidence: 95%
“…If we had considered σ to be a single value (the classic approach), the margins calculated would have been much smaller than those really needed (except in cases with very tight margins, such as posterior margins in the prostate and prostate bed). This effect was shown by Herschtal et al, although no setup protocol was assumed in that study. Predicted margins were calculated by including systematic errors in the population, with the result that the effects of random errors were less important in that situation.…”
Section: Discussionmentioning
confidence: 99%
“…In‐room volumetric imaging enabled us to have access to huge datasets and, therefore, to analyze the variation in random errors within patients. Herschtal et al showed that heterogeneity in random errors was related to an increase in treatment margins compared with those calculated with the VHF. The fact that patients have different characteristics and that these can be expressed mathematically paves the way for personalized treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have attempted to individualise margins based on patient factors [13][14][15][16]. For example, Thompson et al, found that patients with a higher BMI have less intrafraction displacement of the prostate in the superior-inferior dimension compared with patients with a lower BMI [16].…”
Section: Introductionmentioning
confidence: 99%